Periodic Maintenance Analysis of Diesel Motor Generator Set 900 kVA Power as Backup Energy: Analisis Pemeliharaan Berkala Motor Diesel Generator Set Daya 900 kVA Sebagai Energi Cadangan - Rofiq Salam, Rois Nur; Widodo, Edi (Procedia of Engineering and Life Science, 2024)
In the realm of backup power sources, maintaining the efficiency of generators is paramount for ensuring reliability and availability during power outages. This study aims to evaluate generator efficiency through routine maintenance analysis, adhering to regulatory frameworks outlined in regulations such as Regulation No. 29 of 2012 and Electricity Law No. 30 of 2009. By employing methods including Mean Time Between Failures (MTBF) and assessing Actual Operating Time (AOT) against Specified Operating Time (SOT), this research determines the availability and compliance of each generator. Results highlight the importance of stringent regulatory compliance in enhancing the functionality and reliability of generators, thereby emphasizing the significance of routine maintenance for improved operational health. Highlight : Adherence to regulatory frameworks ensures operational compliance and reliability. Routine maintenance analysis enhances generator efficiency and availability. Availability assessment methods such as MTBF and AOT provide insights into operational health. Keywords: Generator reliability, Routine maintenance, Regulatory compliance, Availability assessment, Backup power sources